STRATEGI PEMBANGUNAN DAERAH DALAM MENINGKATKAN MUTU SUMBER DAYA ALAM DAN SUMBER DAYA MANUSIA - Nasution, Ade Parlaungan (Fakultas Ekonomi dan Bisnis Universita Labuhanbatu Sumatera Utara Indonesia, 2020)
The implementation of regional development requires accurate planning so that it is hoped that regional governments can evaluate the development strategies they are doing. In line with the rapid pace of development in the regions, data and development indicators are needed in accordance with predetermined development plans and strategies. Natural resources are important assets in driving the wheels of development in an area. The aspect of utilizing natural resources is a very strategic matter in determining the amount of revenue or the level of its contribution in the formation of regional development capital. Management of natural resources in the perspective of Regional Autonomy is basically the power sharing of the authority for managing natural resources between the Government and Provinces and Regencies / Cities. In addition, the quality of human resources is an important component in every move of a regional development strategy. High-quality human resources can accelerate regional development. In order to become a formidable human resource, the population must have sufficient quality so that it can become an effective development capital. Without an increase in quality, the large population will cause various problems and become a burden for development. Development efforts through a planned regional development strategy can produce the expected achievement of development goals. Appropriate planning in accordance with the conditions in an area is an absolute requirement for regional development efforts. In addition, collaboration with the principle of partnership between government and society is an important aspect that needs to be considered in implementing development strategies area.